Multiple types of childhood and adult violence among homeless and unstably housed women in San Francisco - Wong, Lauren H. (Violence Vict, 2016)
The present study examined the relationship between different forms of childhood violence (emotional, physical, and sexual) and these same forms of violence in adulthood, using a cross-sectional baseline survey of 298 homeless and unstably housed women in San Francisco, California. We also examined other related factors, including mental illnesses diagnosis, sex exchange, jail time, HIV status, and sociodemographic information. Regression analysis indicated that while several of these factors were associated with experiences of violence as an adult, specific types of child violence (e.g. sexual violence) predicted instances of that same type of violence as an adult, but not necessarily other types. Thus, risk of adult violence among low-income women may be better predicted and addressed through histories of same-type childhood violence, despite competing current stressors.